N-Acetylation of methyl hydrazones with acetic acid in presence of PdCl2. Issue 10 (19th May 2023) - Aslanoglu, Furgan; Sahin, Ertan
Abstract: Organic compounds such as acetic anhydride or acetyl chloride are generally used to form amide bonds by the acetylation of a nitrogen atom. However, it is not possible to use this traditional method for hydrazine derivatives. In this article, a new synthesis method has been developed for the formation of a new amide bond via the acetylation of methyl hydrazones with acetic acid. In the development of this unprecedented synthesis method, more than one catalyst was used as the Lewis acid. PdCl2 was identified as the most suitable catalyst for this reaction. In addition, more than one solvent experiment was carried out for the optimization of this method and experiments were carried out to provide the most optimal conditions for catalyst loading. In addition, the applicability of this method to various hydrazone derivatives was tested. The structures of nine new amide bond-containing acetylated methyl hydrazones prepared by this synthesis method were elucidated using 1D-NMR, 2D-NMR, LCMS and X-Ray. Graphical Abstract: UF0001